ANALISIS PENGARUH KUALITAS LAYANAN TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN SEBAGAI VARIABEL INTERVENING PADA PENGGUNA JASA KERETA API DI KABUPATEN PURWOREJO - Agus Fitri Yanto (Politeknik Sawunggalih Aji, 2018)
The purpose of this study was to determine the significance of the influence of reliability,responsiveness, assurance, emphaty and tangible to service user loyalty Sawunggalih Train BusinessClass at Purworejo with satisfaction as an intervening variable. Analysis tool used is the path analysis. With the F test for equation 1, we know that in unison reliability, responsiveness, assurance,emphaty and tangible significant effect on consumer satisfaction. The F test for equation 2, in unisonreliability, responsiveness, assurance, emphaty, tangible and satisfaction have a significant effect onconsumer loyalty Sawunggalih Train Business Class. Through this study is known too that the reliability,assurance, emphaty no significant effect on satisfaction. Then responsiveness and tangible, positive andsignificant impact on satisfaction. Reliability and tangible does not have a significant effect on consumerloyalty. The responsiveness has negative significant effect on loyalty. While assurance, satisfaction andemphaty proved a significant effect on consumer loyalty. Based on the results of impact analysis of direct and indirect, the indirect path tangible andsignificant positive impact on customer loyalty through satisfaction with the regression coefficient or thehighest effect and has a strong correlation. So is most appropriate path is selected than any other point inan effort to increase consumer loyalty.